Educational Challenges in the Digital Age: The Case Study of Using ChatGPT by Madrasah Educators in Indonesia - Zuzana, Mira (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to explore and analyse the challenges of education in the digital era in the use of ChatGPT by Madrasah Aliyah (MA) and Madrasah Tsanawiyah (MTs) educators in Indonesia. This study uses a type of qualitative research method that is field research. Field research is research with data sourced from the field. The data sources include primary data derived from the results of interviews and secondary data derived from the results of the review of library materials such as scientific articles (journal), books, etc. related to the research topic. Data collection techniques in field research by means of interviews and documentation. The data found were analysed using the Miles and Huberman technique, namely data condensation, data presentation, and conclusion drawing. This study found that the use of ChatGPT by educators has several challenges including potential dependence on technology, ethics and privacy, bias in AI infrastructure readiness and technology accessibility. The research contributes to the development of the use of ChatGPT by MA and MTs educators in Indonesia in the digital era.